Partial unilateral lentiginosis in a 17-year-old girl. - Ramalingam, S.; Haripraba, A.; Karunanandhan, M.; Singh, Y. (European Journal of Pediatric Dermatology, 2024)
Partial unilateral lentiginosis presents as multiple lentigines confined to one side of the body; sometimes the lentigines may have a zosteriform distribution. The current paper describes the case of a 17-year-old girl with partial unilateral lentiginosis present on the right hemithorax and abdomen in the T4-T12 dermatomes and extending to the right back without crossing the midline; the differential diagnosis is discussed especially with respect to nevus spilus.